Pengaruh Model Pembelajaran dan Gaya Kognitif Peserta Didik Terhadap Kesadaran Sejarah di SMAN 5 Tambun Selatan - Fitri Windayani (Jurnal Pendidikan Sejarah, 2016)
The aim of study is to reveal the influence of instructional model and cognitive style on historical conciousness on SMAN 5 Tambun Selatan.The methodology used is the experimental method with treatment by level ANAVA 2 X 2. Reseach instrumentation will include a test that will be used to measure students historical conciousness from instructional model and cognitive style of students. A total participant from experiment class are 33 student and from controll class are 30 students will be selected. Data analysis be performed by using two way varians analysis. Among the result of this research are the historical conciousness of students who follow discovery instructional model higher than the student who studied with direct instruction model, the historical conciousness of students who have field independent cognitive style higher than than student who have a field dependent cognitive style and there is an interaction between models of instructional and cognitive style.